Ann-Based Model Predictive Controller to Reduce Chattering of Horizontal Milling Machine - Dina Mohamed Hafez Ibrahim; Ahmed. A. Aboelsoud (2025)
Milling process is widely used in industry for the manufacturing of mechanical parts. In this thesis the horizontal milling machines is proposed. Also, in this thesis considers the chattering phenomenon exhibited by horizontal milling machine which leads to poor surface finish on the work piece, shortened tool life, and possible machine damage, and presents a solution to reduce its effect in the f02orm of feedback control. The contribution of this thesis is twofold. First the condition of oscillation which causes chattering is derived. The inherent delay in the dynamics of the horizontal milling machine is the cause of oscillations under certain conditions and presented in the form of stability chart. Second an Artificial Neural Network (ANN) based on Model Predictive Controller (MPC) is proposed to reduce the chattering phenomenon.
(3JJfGhd gPg GdQSGdI XGgQI GdJPHPHGJ GdJQOOjI GdJj JXgQgG BdI GdJaQjR GdCabjI hGdJj JDOj Edi ShA JTWjH SWM bWYI GdYed, hJbUjQ YeQ GdCOGI, hGMJeGd Jda GdBdI, hJbOe MdkG dJbdjd JCKjQgG aj Tcd GdJMce aj QOhO GdaYd(B. (3Ef GdJCNjQ GdeJCUd aj OjfGejcjGJ BdI GdJaQjR GdCabjI gh SHH GdJPHPHGJ aj Xd XQha eYjfI(B. (3eSGgeI gPg GdQSGdI PGJ Tbjf(B. (3ChdG jJe GTJbGb MGdI GdJPHPH GdJj JSHH GdGgJRGRGJ GdJQOOjI hYQVgG aj eNWW GdGSJbQGQ(B. (3KGfkjG, Je GbJQGM fehPL JMce JfHDj jYJeO Ydi GdTHcI GdYUHjI UfGYjI dJbdjd XGgQI GdGgJRGRGJ GdJQOOjI(B. (3jdJbW fehPL GdJMce OjfGejcjGJ BdI GdJaQjR, hYdi CSGSgG Je JUeje hMOI GdJMce GdJfHDj(B. (3JXgQ fJGFL GdeMGcGI HGSJNOGe GdeGJdGH aYGdjI hMOI GdJMce GdebJQMI hJbdd HGdaYd ef GdJThjT ebGQfI HGdJMce aj GdMdbI GdeaJhMI(B.s
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 53-56.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Communication Engineering; (3gfOSI GdGJUGdGJ s; Milling machine -- chattering -- Model predictive control -- artificial neural networks